Gas-sensitive material as well as preparation method and application thereof
By combining CoxNi3-x (HITP)2 bimetallic MOF material with the golden cross finger electrode, a gas sensor is formed, which solves the problem of difficulty in detecting H2S gas in a long-term stable manner under high operating temperature and an oxygen-free atmosphere in the prior art, and achieves excellent selectivity and long-term stability, which is suitable for mass production and applications in an oxygen-free environment.
Patent Information
- Application Number
- CN202311227173.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to detect H2S gas stably for a long time under high operating temperature and oxygen-free atmosphere, and the sensor has problems such as poor selectivity, irreversibility and high power consumption.
CoxNi3-x (HITP)2 is used as the gas-sensitive material, and bimetallic MOF material is prepared by solvothermal method and combined with the golden cross finger electrode to form a gas sensor. The material has excellent electrical conductivity and chemical stability, and can detect H2S gas for a long time in an oxygen-free environment.
It realizes long-term stable detection of H2S gas under room temperature conditions, has excellent selectivity and repeatability, is suitable for mass production, and shows good sensing performance in an oxygen-free environment.
Smart Images

Figure CN119688792A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gas sensors, and in particular relates to a gas-sensitive material and a preparation method and application thereof. Background Art
[0002] Long-term stable detection of hydrogen sulfide (H2S) gas at room temperature is of great engineering significance for electrical equipment using sulfur hexafluoride (SF6) as the main insulating gas. During long-term use, insulation defects such as metal particle defects, metal protrusion defects, and air gap defects may appear in electrical equipment. These defects will cause partial discharge, causing SF6 gas to decompose into H2S, SO2, CO2, SO2F2, SOF2, SOF4 and HF, etc. These byproducts will weaken the insulation performance of SF6, corrode electrical equipment, and cause SF6 leakage. A relatively small amount of SF6 may also have a certain impact on global climate change.
[0003] H2S is a typical decomposition product of SF6. The working condition of electrical equipment can be judged by long-term detection of H2S concentration. It is difficult for gas sensors in the prior art to break through the serious limitations of high operating temperature and drift problems that have existed for a long time in practical applications. Conventional gas analysis techniques, such as gas chromatography and mass spectrometry, allow reliable detection and identification of trace-level gases. However, the inherent bulkiness, inconvenience and high cost seriously hinder their widespread application. The reported H2S sensors based on SMOXs (such as WO3, Ga2O3, SnO2, ZnO, etc.) have high sensitivity, but still have the disadvantages of being unable to be used in an oxygen-free atmosphere, the low specific surface area causing some sensors to be irreversible, resulting in the inability to use the sensors for a long time, poor selectivity and high operating temperature. From the perspective of long-term development and intelligent applications, such sensors not only increase the power consumption of the system but are also not conducive to integration. Summary of the invention
[0004] In view of the deficiencies in the prior art, a first object of the present invention is to provide a gas-sensitive material having excellent H2S gas detection selectivity and long-term stability and having important engineering application value.
[0005] The second object of the present invention is to provide a method for preparing the above-mentioned gas-sensitive material, which is simple, highly repeatable, and suitable for mass production.
[0006] The third object of the present invention is to provide a gas sensor, which includes the above-mentioned gas sensitive material and gold interdigital electrodes.
[0007] The fourth object of the present invention is to provide a method for preparing the above-mentioned gas sensor.
[0008] A fifth object of the present invention is to provide an application of the above-mentioned gas sensor, wherein the gas sensor can be used to detect H2S gas in an oxygen-free environment.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] A gas-sensitive material, the chemical formula of which is Co x Ni 3-x (HITP)2, wherein x is 0.6-2.4.
[0011] The preparation method of the above-mentioned gas-sensitive material comprises the following steps:
[0012] (3) dissolving a cobalt ion source and a nickel ion source in an organic solvent;
[0013] (4) Adding HATP·6HCl aqueous solution and NaOAc aqueous solution to the reaction system obtained in step (1), stirring for reaction, and then drying to obtain the gas-sensitive material.
[0014] Furthermore, in step (1), the cobalt ion source is Co(NO3)2·6H2O, the nickel ion source is Ni(OAc)2·4H2O; and the organic solvent is DMF;
[0015] In step (2), the mass volume ratio of HATP·6HCl to water in the HATP·6HCl aqueous solution is 1 mg:0.3 mL; the concentration of the NaOAc aqueous solution is 2 mol·L -1 ; The mass volume ratio of the HATP·6HCl to the NaOAc aqueous solution is 1 mg:0.4 mL; the stirring reaction temperature is 65°C, the speed is 500 r / min, and the time is 2 h; the drying temperature is 65°C. ;
[0016] Furthermore, the mass volume ratio of the Co(NO3)2·6H2O, Ni(OAc)2·4H2O, organic solvent and NaOAc aqueous solution is (0.8-3.25) mg: (0.7-2.78) mg: 3 mL: 2 mL.
[0017] The present invention is based on the ligand 2,3,6,7,10,11-hexamidotriphenylhexahydrochloride (HATP·6HCl) and divalent metal ions (Co 2+ or Ni 2+ ) were combined with a solvothermal method to prepare bimetallic Co x Ni 3-x(HITP)2. The central metal is tetracoordinated with the N atom from the ligand HATP·6HCl by bidentate chelation. The ligands and metals are alternately connected to form an infinitely extended two-dimensional plane, which is then superimposed through π-π interactions to form a layer-honeycomb lattice alternating with a two-dimensional hexagonal slip parallel layer structure.
[0018] A gas sensor, comprising the above-mentioned gas sensitive material and gold interdigital electrodes (Auinterdigital electrodes, IDEs); the size of the gold interdigital electrodes is greater than or equal to 3*4.5mm 2 .
[0019] Furthermore, the gold interdigitated electrode is prepared by the following steps:
[0020] (1) Cleaning and drying the silicon wafer, and sputtering the Cr layer and the Au layer;
[0021] (2) performing photolithography on the silicon wafer obtained in step (1) to obtain a silicon wafer with a photolithography pattern;
[0022] (3) The silicon wafer obtained in step (2) is processed by ion beam processing to form 50 pairs of 130 nm thick and 10 μm wide Cr / Au lines with a line spacing of 10 μm, and then diced into 3×4.5 mm 2 The gold interdigitated electrodes are kept aside.
[0023] Furthermore, in step (1), the thickness of the Cr layer is 30 nm, and the thickness of the Au layer is 100 nm.
[0024] The preparation method of the above-mentioned gas sensor comprises grinding the gas-sensitive material with anhydrous ethanol, coating the grinding material on the surface of a gold interdigital electrode, and obtaining the gas sensor.
[0025] Application of the above gas sensor: the gas sensor can be used to detect H2S gas.
[0026] Furthermore, the gas sensor can detect H2S gas in an oxygen-free environment.
[0027] Beneficial effects:
[0028] 1. Co provided by the present invention 1.8 Ni 1.2 The (HITP)2 gas-sensitive material has excellent electrical conductivity and can still show excellent chemical stability when immersed in an acidic aqueous solution for a long time. Its performance is significantly better than that of conventional MOF materials. The reported bulk conductivity of Ni3(HITP)2 exceeds that of activated carbon and porous graphite, while the bimetallic Co x Ni3-x The electrical conductivity of the (HITP)2 material is higher than that of Ni3(HITP)2; the Co 1.8 Ni 1.2 (HITP)2 material can detect H2S gas stably and for a long time in an oxygen-free atmosphere, making it possible to monitor H2S in a space capsule and thus monitor the operating status of the battery, which is of great significance for the successful completion of space exploration.
[0029] 2. The present invention uses a two-dimensional MOF material, namely Co x Ni 3-x The preparation of gas sensors using (HITP)2 as carrier materials first overcomes the disadvantages of inconvenient application and high cost of conventional gas chromatography and mass spectrometry; secondly, it breaks through the limitations of low specific surface area, poor selectivity and high operating temperature of H2S gas sensors based on SMOXs in the prior art. More importantly, SMOXs gas sensors require oxygen adsorption to establish an electronic core-shell configuration, thereby causing changes in resistance and responding to target gases, so they cannot be used in an oxygen-free atmosphere. x Ni 3-x (HITP)2 gas-sensitive materials have both a pre-designable and highly ordered structure, inherent porosity and rich physical and chemical properties, and break through the limitations of traditional MOF materials, which are usually electrical insulators.
[0030] 3. The gas sensor provided by the present invention is made of two-dimensional MOF material (Co x Ni 3-x (HITP)2) and gold interdigital electrodes; the gas sensor is a sensor made of pure MOF as a gas-sensitive active material without adding other conductive components. The preparation method of the gas sensor is simple, easy to operate, highly repeatable, and the device volume is only 3*4.5mm 2 , suitable for mass production, with important application value; the Co x Ni 3-x The preparation process of (HITP)2 gas sensitive materials and gold interdigital electrodes is simple, can be prepared in batches, and is easy to integrate.
[0031] 4. The gas sensor provided by the present invention has excellent selectivity for H2S and shows negligible cross response. Its sensitivity drifts by only 3.27% after working for 2 months at room temperature. It still shows excellent sensing performance under anaerobic conditions with N2 and SF6 as background gases, and its performance is significantly better than that of SMOXs gas sensors that can only work in an oxygen-containing environment. The gas sensor provided by the present invention can be used in the field of real-time dynamic monitoring of H2S gas decomposed from SF6, providing predictions for maintenance personnel and avoiding fatal failures of electrical equipment, which has important engineering significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The SEM and TEM images of the gas-sensitive materials prepared in Examples 1-5 and Comparative Examples 1-2; Figure 1 a is the SEM image of the gas-sensitive material prepared in Comparative Example 1; Figure 1 bf are SEM images of the gas-sensitive materials prepared in Examples 1-5, respectively; Figure 1 g is the SEM image of the gas-sensitive material prepared in Comparative Example 2; Figure 1 h is Co prepared in Example 4 1.8 Ni 1.2 TEM image of (HITP)2 gas-sensitive material;
[0033] Figure 2 This is a schematic diagram of the gold interdigitated electrode prepared in Example 6;
[0034] Figure 3 Co prepared in Example 4 1.8 Ni 1.2 XRD pattern of (HITP)2 gas-sensitive material; Figure 3 a is Co 1.8 Ni 1.2 (HITP)2 XRD pattern of fresh material, Figure 3 b is the Co after testing H2S for 60 days 1.8 Ni 1.2 XRD pattern of (HITP)2 gas-sensitive material;
[0035] Figure 4 This is a graph showing the H2S gas response of the gas sensor prepared in Example 7;
[0036] Figure 5 This is a H2S gas detection stability curve of the gas sensor prepared in Example 7;
[0037] Figure 6 This is a graph showing the H2S gas detection selectivity of the gas sensor prepared in Example 7. DETAILED DESCRIPTION
[0038] In order to further describe the present invention in detail, the following specific implementation examples are given, but they are only used to illustrate the present invention and make the steps clearer, rather than to limit the scope of application of the present invention.
[0039] Example 1
[0040] 1. In a glass bottle, dissolve 0.8 mg of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 2.78 mg of nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 3 mL of DMF;
[0041] 2. Then, add 5 mg of HATP·6HCl aqueous solution dissolved in 1.5 mL of water until clear and transparent to the system obtained in step 1, followed by 2 mL of 2 mol·L -1 of NaOAc aqueous solution;
[0042] 3. Place the mixed solution obtained in step 2 in an open glass bottle and react in a digital heating magnetic stirrer at a temperature of 65°C and a speed of 500 r / min for 2 hours;
[0043] 4. The product of step 3 was washed with a large amount of water and filtered, and finally dried in a vacuum drying oven at 65°C to obtain a black powder, which was recorded as Co 0.6 Ni 2.4 (HITP)2.
[0044] Example 2
[0045] 1. In a glass bottle, dissolve 1.63 mg Co(NO3)2·6H2O and 2.09 mg nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 3 mL DMF;
[0046] 2. Then, add 5 mg of HATP·6HCl aqueous solution dissolved in 1.5 mL of water until clear and transparent to the system obtained in step 1, followed by 2 mL of 2 mol·L -1 of NaOAc aqueous solution;
[0047] 3. Place the mixed solution obtained in step 2 in an open glass bottle and react in a digital heating magnetic stirrer at a temperature of 65°C and a speed of 500 r / min for 2 hours;
[0048] 4. The product of step 3 was washed with a large amount of water and filtered, and finally dried in a vacuum drying oven at 65°C to obtain a black powder, which was recorded as Co 1.2 Ni 1.8 (HITP)2.
[0049] Example 3
[0050] 1. In a glass bottle, dissolve a mixed solution of 2 mg Co(NO3)2·6H2O and 1.74 mg nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 3 mL DMF;
[0051] 2. Then, add 5 mg of HATP·6HCl aqueous solution dissolved in 1.5 mL of water until clear and transparent to the system obtained in step 1, followed by 2 mL of 2 mol·L -1 of NaOAc aqueous solution;
[0052] 3. Place the mixed solution obtained in step 2 in an open glass bottle and react in a digital heating magnetic stirrer at a temperature of 65°C and a speed of 500 r / min for 2 hours;
[0053] 4. The product of step 3 was washed with a large amount of water and filtered, and finally dried in a vacuum drying oven at 65°C to obtain a black powder, which was recorded as Co 1.5 Ni 1.5 (HITP)2.
[0054] Example 4
[0055] 1. In a glass bottle, dissolve 2.44 mg Co(NO3)2·6H2O and 1.4 mg nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 3 mL DMF;
[0056] 2. Then, add 5 mg of HATP·6HCl aqueous solution dissolved in 1.5 mL of water until clear and transparent to the system obtained in step 1, followed by 2 mL of 2 mol·L -1 of NaOAc aqueous solution;
[0057] 3. Place the mixed solution obtained in step 2 in an open glass bottle and react in a digital heating magnetic stirrer at a temperature of 65°C and a speed of 500 r / min for 2 hours;
[0058] 4. The product of step 3 was washed with a large amount of water and filtered, and finally dried in a vacuum drying oven at 65°C to obtain a black powder, which was recorded as Co 1.8 Ni 1.2 (HITP)2.
[0059] Figure 3 The Co prepared in this example 1.8 Ni 1.2 XRD pattern of (HITP)2 gas-sensitive material, Figure 3 a is the refined XRD pattern of fresh material. Figure 3 b is the use of Co x Ni 3-x The refined XRD pattern of (HITP)2 after testing H2S for 60 days shows that its structure has not changed after 60 days of long-term stability testing, which verifies that Co 1.8 Ni 1.2 (HITP)2 gas-sensitive material has excellent stability to H2S. In addition, the results also confirmed that Co x Ni 3-xCrystal structure of (HITP)2. For MOFs with a Co / Ni ratio of 3:2, diffraction peaks appear at 2θ=4.85°, 9.61° and 12.72° corresponding to the (100), (200) and (130) planes, respectively, indicating that MOFs have long-range order on the ab plane. In addition, the weak peak and plate peak at 27.63° corresponding to the (002) reflection show relatively poor long-range ordered stacking along the crystal c-axis, which is in good agreement with the interlayer van der Waals force of the material. According to the Bragg equation and theoretical simulation analysis, the interlayer distance is calculated to be The same calculation results as the experimental results Highly consistent.
[0060] Example 5
[0061] 1. In a glass bottle, dissolve 3.25 mg Co(NO3)2·6H2O and 0.7 mg nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 3 mL DMF;
[0062] 2. Then, add 5 mg of HATP·6HCl aqueous solution dissolved in 1.5 mL of water until clear and transparent to the system obtained in step 1, followed by 2 mL of 2 mol·L -1 of NaOAc aqueous solution;
[0063] 3. Place the mixed solution obtained in step 2 in an open glass bottle and react in a digital heating magnetic stirrer at a temperature of 65°C and a speed of 500 r / min for 2 hours;
[0064] 4. The product of step 3 was washed with a large amount of water and filtered, and finally dried in a vacuum drying oven at 65°C to obtain a black powder, which was recorded as Co 2.4 Ni 0.6 (HITP)2.
[0065] Example 6
[0066] Preparation of gold interdigitated electrodes (IDEs)
[0067] 1. Clean the silicon wafer and dry it in an oven, then sputter a layer of Cr / Au with a thickness of 30 / 100 nm on the silicon wafer, where the Cr layer plays an adhesion role;
[0068] 2. Use LC100A photoresist to pattern the substrate, spin-coat LC100A photoresist on the silicon wafer at a speed of 1000 r / min for 30 seconds, and then transfer the silicon wafer to a 110°C hot plate and heat it for 90 seconds;
[0069] 3. Transfer the silicon wafer to the photolithography machine, and expose the wafer for 7.5 seconds after the mask is loaded. After exposure, remove the silicon wafer and place it in the cleaning rack to develop it in the developing tank for 45 seconds. During this period, shake it continuously to ensure sufficient development. After development, rinse the silicon wafer in clean water and spin dry. Next, bake the silicon wafer in a 135℃ oven for 30 minutes, and finally form a photolithography pattern with a thickness of about 2.4μm on the silicon wafer.
[0070] 4. Use ion beam processing technology to etch down 130nm on the silicon wafer to remove excess Cr / Au. The IDEs formed after plasma stripping contain 50 pairs of 130nm thick and 10μm wide Cr / Au lines with a line spacing of 10μm;
[0071] 5. Etch away the photoresist and slice into pieces with a size of 3×4.5mm 2 The chip is spare.
[0072] Figure 2 is a schematic diagram of the gold interdigital electrode prepared in this embodiment, Figure 2 In the figure, 1 is silicon wafer and 2 is IDEs.
[0073] Example 7
[0074] The gas sensor was prepared using the following steps:
[0075] First, the Co prepared in Example 1-5 0.6 Ni 2.4 (HITP)2、Co 1.2 Ni 1.8 (HITP)2、Co 1.5 Ni 1.5 (HITP)2、Co 1.8 Ni 1.2 (HITP)2、Co 2.4 Ni 0.6 (HITP)2 and Ni3(HITP)2 prepared in comparative example 1 were ground into uniform pastes with anhydrous ethanol respectively, and the pastes were evenly coated on the surface of the gold interdigital electrode prepared in example 6 with a brush. After the ethanol evaporated, a gas sensor was obtained.
[0076] Comparative Example 1
[0077] Preparation of Ni3(HITP)2 Materials
[0078] 1. Dissolve 3.5 mg of nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 1.5 mL of DMSO;
[0079] 2. Then add 5 mg of HATP·6HCl aqueous solution dissolved in 1.5 mL of water until clear and transparent, followed by 2 mL of 4 mol·L -1 of NaOAc aqueous solution;
[0080] 3. Place the mixed solution in an open glass bottle and react for 2 hours in a digital heating magnetic stirrer at a temperature of 65°C and a speed of 500 r / min;
[0081] 4. Wash with plenty of water and methanol and filter, dry in a vacuum drying oven at 65°C to obtain a black powder, recorded as Ni3(HITP)2.
[0082] Comparative Example 2
[0083] 1. Take 27.1 mg of Co(NO3)2·6H2O and dissolve it in 1.5 mL of DMF;
[0084] 2. Then add 5 mg of HATP·6HCl aqueous solution dissolved in 1.5 mL of water until clear and transparent, followed by 2 mL of 2 mol·L -1 of NaOAc aqueous solution;
[0085] 3. Place the mixed solution in an open glass bottle and react for 2 hours in a digital heating magnetic stirrer at a temperature of 65°C and a speed of 500 r / min;
[0086] 4. Finally, wash with a large amount of water and filter, and finally dry in a vacuum drying oven at 65°C to obtain a black powder, which is recorded as Co 3( HITP)2.
[0087] Figure 1 The SEM and TEM images of the gas-sensitive materials prepared in Examples 1-5 and Comparative Examples 1-2 are shown in FIG. Figure 1 a is the SEM image of the gas-sensitive material prepared in Example 1, Figure 1 bf are SEM images of the gas-sensitive materials prepared in Examples 1-5, respectively. The results show that Co x Ni 3-x (HITP)2 (x = 0.6, 1, 2, 1.5, 1.8, 2.4) has a similar rod-like structure; Figure 1 h is Co prepared in Comparative Example 2 1.8 Ni 1.2 TEM image of (HITP)2.
[0088] Performance Testing
[0089] The H2S gas testing method is:
[0090] The test system of the gas sensor is composed of a gas distribution system, a gas mixing chamber, a test cavity, a data acquisition device and a computer. The concentration of the target gas is obtained by a self-built gas distribution system. In the present invention, SF6 and N2 are used as background gases. The entire experiment is carried out at room temperature. The data acquisition device is connected to the computer, and the computer is used to collect and process the output data of the gas sensor. Before the test, the background gas is introduced to make the output of the gas sensor stable, and then a certain concentration of the target gas and the background gas are introduced into the gas mixing chamber for mixing, and finally introduced into the test cavity and the output resistance of the gas sensor is collected. The gas-sensitive performance of the prepared gas sensor is evaluated by recording the resistance change in different gases. The gas sensor response is defined as S=△R / R0, △R=R-R0, where R0 and R represent the resistance of the sensor in SF6 / N2 and the target gas, respectively. 1. Test of gas detection performance at room temperature without oxygen
[0091] The Co-containing 1.8 Ni 1.2 (HITP)2 gas sensitive material gas sensor detects H2S gas. The results are as follows Figure 4 As shown in the figure, in N2 and SF6 atmospheres, the response values of the gas sensor increase with the increase of gas concentration and show a good linear relationship (R 2 =0.999), where the slope is 45.49%·ppm under N2 atmosphere -1 ) and SF6 atmosphere (the slope is 43.31% ppm -1 ) have significant similarities.
[0092] 2. Stability test
[0093] The Co prepared in Example 7 1.8 Ni 1.2 The gas sensor made of (HITP)2 gas-sensitive material was placed in a 5ppm H2S N2 atmosphere to test the long-term stability of the gas sensor. Figure 5 As shown, the results show that the response curve of the gas sensor changes little over time, and the response drifts only 3.27% between day 0 and day 60. This shows the excellent long-term stability of the room temperature H2S gas sensor.
[0094] 3. H2S selective detection
[0095] Nine typical gases, including ethanol, SO2, acetone, NH3, methanol, CO, trimethylamine (TMA), NO2 and NO, were selected as interfering gases. The response of the gas sensor prepared in Example 7 to the above gases with a concentration of 5 ppm was measured at room temperature. It is worth noting that compared with other interfering gases, Figure 6 Co x Ni 3-x The gas sensor prepared by (HITP)2 gas sensitive material has a higher response to 5ppm H2S, Co 1.8 Ni 1.2 The response of the gas sensor made of (HITP)2 gas sensitive material to 5ppm H2S is 7.5 times that of the gas sensor made of single metal Ni3(HITP)2 gas sensitive material.
[0096] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A gas-sensitive material, characterized in that: The chemical formula of the gas-sensitive material is Co x Ni 3-x (HITP)2, wherein x is 0.6-2.
4.
2. A method for preparing the gas-sensitive material according to claim 1, characterized in that: The preparation method adopts the following steps: (1) dissolving a cobalt ion source and a nickel ion source in an organic solvent; (2) Adding HATP·6HCl aqueous solution and NaOAc aqueous solution to the reaction system obtained in step (1), stirring for reaction, and then drying to obtain the gas-sensitive material.
3. The preparation method according to claim 2, characterized in that: The mass volume ratio of the cobalt ion source, the nickel ion source, the organic solvent and the NaOAc aqueous solution is (0.8-3.25) mg: (0.7-2.78) mg: 3 mL: 2 mL.
4. The preparation method according to claim 2, characterized in that: In step (1), the cobalt ion source is Co(NO3)2·6H2O, the nickel ion source is Ni(OAc)2·4H2O; and the organic solvent is DMF; In step (2), the mass volume ratio of HATP·6HCl to water in the HATP·6HCl aqueous solution is 1 mg:0.3 mL; the concentration of the NaOAc aqueous solution is 2 mol·L -1 The mass volume ratio of the HATP·6HCl to the NaOAc aqueous solution is 1 mg:0.4 mL; the stirring reaction temperature is 65°C, the rotation speed is 500 r / min, and the time is 2 h; the drying temperature is 65°C.
5. A gas sensor, characterized in that: The gas sensor comprises the gas-sensitive material and gold interdigital electrodes as claimed in claim 1; the size of the gold interdigital electrodes is greater than or equal to 3*4.5 mm 2 .
6. The gas sensor according to claim 5, characterized in that: The gold interdigitated electrode is prepared by the following steps: (1) Cleaning and drying the silicon wafer, and sputtering the Cr layer and the Au layer; (2) performing photolithography on the silicon wafer obtained in step (1) to obtain a silicon wafer with a photolithography pattern; (3) The silicon wafer obtained in step (2) is processed by ion beam processing to form 50 pairs of 130 nm thick and 10 μm wide Cr / Au lines with a line spacing of 10 μm, and then diced into 3×4.5 mm 2 The gold interdigitated electrodes are kept aside.
7. The gas sensor according to claim 6, characterized in that: In step (1), the thickness of the Cr layer is 30 nm, and the thickness of the Au layer is 100 nm.
8. The method for preparing a gas sensor according to any one of claims 5 to 7, characterized in that: The preparation method comprises grinding the gas-sensitive material with anhydrous ethanol, coating the mixture on the surface of a gold interdigital electrode, and obtaining the gas sensor.
9. Use of the gas sensor according to any one of claims 5 to 7 and / or the gas sensor prepared by the method according to claim 8, characterized in that: The gas sensor can be used to detect H2S gas.
10. The use according to claim 9, characterized in that: The gas sensor can detect H2S gas in an oxygen-free environment.